Performance measurement of the complaint and failure management process. Issue 1 (2nd January 2020) - Ruessmann, Maximilian; Hellebrandt, Thomas; Heine, Ina; Huber, Ulrich; Telpis, Vanya; Rutten, Paul; Schmitt, Robert H.
Abstract: In this paper, we empirically investigate linkages between the performance of the complaint and failure management (CFM) process and its potentially influencing factors. In contrast with earlier literature, we consider the CFM process holistically, while in the past it was only partially in focus (e.g., customer relationship management). We are interested to answer two questions: (1) What factors influence CFM process performance? (2) Does the implementation of CFM performance measures correlate positively with CFM process performance? First, to answer these questions, we conceptualized constructs theoretically related to CFM process performance and validated the measurement instrument. Second, we carried out non-parametric tests of correlation (Spearman) to investigate relationships between the constructs based on the data of a survey study among 77 companies. The findings provide empirical evidence that CFM performance measurement, data orientation and management attention positively influence CFM process performance. Additionally, we identified process maturity as lever for performance improvements. In this regard, we provide a CFM process maturity measure consisting of three main phases: "data collection and organization", "failure valuation and elimination" and "implementation and knowledge transfer". Our analyses showed that correlation findings are highly dependent on company size and only hold for companies with more than 1, 000 employees.